Methanesulfonate salt of triazolopyrazine derivative

By developing new methanesulfonate compounds of triazolopyrazine derivatives, the problems of low storage stability and light stability are solved, and processability improvement and pharmacological activity are achieved during drug preparation.

CN119451966APending Publication Date: 2025-02-14AI BEI & CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380050229.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2023-05-03
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The pure substance storage stability and light stability of triazolopyrazine derivatives lead to poor processability during drug preparation.

Method used

Develop novel methanesulfonate compounds of triazolopyrazine derivatives to inhibit the activity of c-Met kinase by binding to hepatocyte growth factors and improve storage stability and photostability.

Benefits of technology

The new methanesulfonate compound effectively inhibits the activity of c-Met kinase, improves the storage stability and light stability of drugs, and improves the processability of drug preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451966A_ABST
    Figure CN119451966A_ABST
Patent Text Reader

Abstract

The present invention relates to a salt of methanesulfonic acid and a triazolopyrazine derivative of chemical formula 1 (mesylate), a pharmaceutical composition comprising said salt, a process for the preparation of said salt and the therapeutic use of said salt. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] As is known in the past, triazolopyrazine derivatives are substances useful for treating hyperproliferative diseases by inhibiting the activity of c-Met kinase. However, in existing literature, many of these triazolopyrazine derivatives are proposed in free base form rather than in salt form.

[0002] In order to improve the pharmacological use of the free base form of triazolopyrazine derivatives, a salt form is required. Therefore, the present invention aims to provide a mesylate salt and a preparation method thereof which maintain the pharmacokinetic and pharmacological activities of the free base form and improve useful physical properties. Background Art

[0003] The present invention relates to a novel mesylate compound of a triazolopyrazine derivative represented by the following chemical formula 1, a preparation method thereof and a pharmaceutical composition containing the same.

[0004] Chemical formula 1:

[0005]

[0006] The present inventors have found the above-mentioned compound having inhibitory activity against tyrosine kinase, and have made great efforts to research and develop a composition for effectively preventing or treating various hyperproliferative disorders caused by abnormal tyrosine kinase activity. As a result, the present inventors have found that a novel salt compound of the compound of Chemical Formula 1, which has been unknown so far, retains the function of the compound in inhibiting the activity of c-Met kinase and improves the storage stability and photostability of the compound, thereby completing the present invention.

[0007] According to the present invention, the novel mesylate compound of the compound of Chemical Formula 1 of the present invention activates phosphorylation by binding to hepatocyte growth factor (HGF), thereby significantly inhibiting the activity of c-Met kinase that triggers cell proliferation, migration, and angiogenesis.

[0008] Therefore, the salt compound of the present invention can be usefully used for treating or preventing various abnormal proliferative diseases mediated by excessive angiogenesis activated by abnormal cell proliferation.

[0009] Furthermore, the novel mesylate salt compound of the compound of Chemical Formula 1 exhibits physical properties different from those of the pure compound, for example, melting point, hygroscopicity, solubility, flow properties or thermodynamic stability.

[0010] Therefore, the salt compound of the compound of Chemical Formula 1 provided by the present invention can be used to select the most suitable form for pharmacological use in the preparation process of medicine or the preparation process of a single pharmaceutical dosage form such as tablets, capsules, ointments, suspensions, or the preparation of a pharmaceutical form with optimal pharmacokinetic properties.

[0011] According to another embodiment of the present invention, the present invention provides a pharmaceutical composition comprising a therapeutically effective amount of the novel mesylate compound of Chemical Formula 1. For example, the present invention provides a pharmaceutical composition for preventing or treating hyperproliferative disorders, comprising the novel salt compound of the compound of Chemical Formula 1 as an active ingredient.

[0012] In this specification, the term "hyperproliferative disorder" refers to a pathological state caused by excessive cell growth, division and migration in a normally growing animal body that is not regulated by the usual restriction method. Hyperproliferative diseases prevented or treated with the composition of the present invention include, for example, cancer, diabetic retinopathy, retinopathy of prematurity, corneal transplant rejection, neovascular glaucoma, skin erythema, proliferative retinopathy, psoriasis, rheumatoid arthritis, osteoarthritis, autoimmune diseases, Crohn's disease, restenosis, atherosclerosis, intestinal adhesions, ulcers, cirrhosis, glomerulonephritis, diabetic nephropathy, malignant nephrosclerosis, thrombotic microangiopathy, organ transplant rejection and glomerular disorders, but are not limited thereto, including all hyperproliferative diseases caused by abnormal cell proliferation and excessive generation of new blood vessels.

[0013] More preferably, the cancer that is one of the abnormal proliferative diseases that can be prevented or treated with the composition of the present invention is lung cancer, gastric cancer, pancreatic cancer, colorectal cancer, ovarian cancer, renal cell carcinoma, prostate cancer or brain tumor.

[0014] When the composition of the present invention is prepared into a pharmaceutical composition, the pharmaceutical composition of the present invention comprises a pharmaceutically acceptable carrier. The pharmaceutically acceptable carrier contained in the pharmaceutical composition of the present invention is a commonly used carrier during preparation, including lactose, glucose, sucrose, sorbitol, mannitol, starch, gum arabic, calcium phosphate, alginate, gelatin, calcium silicate, microcrystalline cellulose, polyvinyl pyrrolidone, cellulose, water, syrup, methylcellulose, methyl hydroxybenzoate, propyl hydroxybenzoate, talc, magnesium stearate and mineral oil, but is not limited thereto. In addition to the ingredients, the pharmaceutical composition of the present invention may also include lubricants, wetting agents, sweeteners, flavor enhancers, emulsifiers, suspending agents, preservatives, etc.

[0015] The pure substance of the triazolopyrazine derivative represented by the above Chemical Formula 1 is not suitable for preparing a general pharmaceutical composition in terms of physical properties such as solubility and thermal stability.

[0016] Therefore, the present inventors screened various salts to develop salt compounds suitable for preparing pharmaceutical dosage forms that improve the solubility and stability of the triazolopyrazine derivatives, thereby developing novel maleate compounds that continuously maintain the pharmacological activity of the compound and have high solubility and excellent stability. Summary of the invention

[0017] Technical issues

[0018] In order to improve the poor processability of the pure triazolopyrazine derivative represented by the chemical formula 1 in drug preparation due to its low storage stability and photostability, the present invention screens the compound for salts, thereby solving the above problem by developing a novel mesylate salt compound of the compound.

[0019] Technical Solution

[0020] The present invention can improve the storage stability and light stability of the triazolopyrazine derivative (ABN401) represented by the chemical formula 1 by developing a novel mesylate (methanesulfonic acid) compound of the triazolopyrazine derivative.

[0021] Furthermore, the present invention provides a method for preparing the mesylate compound and a pharmaceutical composition containing the mesylate compound as an active ingredient.

[0022] Effects of the Invention

[0023] The present invention relates to a novel mesylate compound of a triazolopyrazine derivative represented by the chemical formula 1 and a preparation method thereof. The novel mesylate compound provided by the present invention improves the usefulness and processability of the compound in drug preparation by improving the storage stability and light stability which are problems existing in pure substances.

[0024] The mesylate compound effectively inhibits the activity of c-Met tyrosine kinase, and can be usefully used as a therapeutic agent for various hyperproliferative diseases associated with excessive cell proliferation and growth due to abnormal kinase activity, such as cancer, psoriasis, rheumatoid arthritis, diabetic retinopathy, etc. In addition, a pharmaceutical composition for inhibiting c-Met tyrosine kinase activity and a pharmaceutical composition for preventing or treating hyperproliferative disorders, comprising the novel salt compound as an active ingredient, are provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Figure 2 is the temperature profile that occurred in the salt screening experiment of the mesylate compound.

[0026] Figure 2 The results of liquid chromatography mass spectrometry using the S19061_03 method with ABN401 as the starting material are shown (retention time = 5.2 min).

[0027] Figure 3 The results of liquid chromatography mass spectrometry using the S19061_01 method and ABN401 as the starting material are shown (retention time = 2.2 min).

[0028] Figure 4 High performance X-ray crystallography (HT-XRPD) patterns of the starting material (Form A), Mes1, Mes2, and Mes3 are shown.

[0029] Figure 5 Shown are high performance X-ray crystallography (HT-XRPD) patterns of Mes1 (Exp. ID SSm4) before (lower) and after (upper) exposure to AAC (40°C / 75%RH) for 2 days.

[0030] Figure 6 shows TGA (A) and TGMS (B) analysis (heating rate 10°C / min) of Mes1 (Exp. ID SSm4). It shows that at a temperature of 25-40°C, a mass loss of 4.3% is caused by acetone and water. Thermal decomposition of the salt is shown at a temperature of about 230°C, and a broad endothermic reaction due to mass loss is shown at a temperature of about 160°C according to the heat flow signal of TGA analysis.

[0031] Figure 7 Shown are high performance X-ray crystallography (HT-XRPD) patterns of Mes2 (Exp. ID SSm5) before (lower) and after (upper) exposure to AAC (40°C / 75%RH) for 2 days.

[0032] Figure 8 shows TGA (A) and TGMS (B) analysis (heating rate 10°C / min) of Mes2 (Exp. ID SSm5). It shows that at temperatures of 25-150°C, 4.5% of mass loss is caused by acetone and water. The heat flow signal according to TGA analysis shows a broad endothermic reaction due to mass loss at a temperature of about 210°C, which may be related to the melting of the anhydrous form due to decomposition.

[0033] Fig. 9The DSC curve of Mes2 (Exp. ID SSm5) is shown (heating rate 10°C / min). The DSC exhibits a broad endothermic reaction at temperatures between 25 and 120°C and another endothermic reaction at 218.2°C, which may be associated with the melting of the anhydrous form.

[0034] Fig.10 The liquid chromatography mass spectrometry analysis of Mes2 (Exp. ID SSm5) is shown. The purity of the active ingredient is 100%.

[0035] Fig.11 Overlay of H-NMR spectra (500 MHz, DMSO-d6) of ABN401 free base (green) and Mes2 (Exp. ID SSm5) (red) is shown. The peak corresponding to CI is fluorescently labeled at the signal at 2.3 ppm. Residual acetone is fluorescently labeled at the peak at 2.1 ppm.

[0036] Fig.12 Shown are high performance X-ray crystallography (HT-XRPD) patterns of Mes3 (Exp. ID SSm6) before (lower) and after (upper) exposure to AAC (40°C / 75%RH) for 2 days.

[0037] Figure 13 shows TGA (A) analysis and TGMS (B) analysis (heating rate 10°C / min) of Mes3 (Exp. ID SSm6). Before thermal decomposition at a temperature of about 220°C, a mass loss of 5.6% was shown due to water. The heat flow signal according to TGA analysis showed a broad endothermic reaction due to mass loss at a temperature of about 200°C.

[0038] Fig.14 High-performance X-ray crystallography (HT-XRPD) patterns of the starting material (Form A), Camp1, and Camp2 are shown.

[0039] Fig.15 Shown are high performance X-ray crystallography (HT-XRPD) patterns of Camp1 (Exp. ID SSm14) before (lower) and after (upper) exposure to AAC (40°C / 75%RH) for 2 days.

[0040] FIG16 shows TGA (A) and TGMS (B) analysis (heating rate 10° C. / min) of Camp1 (Exp. ID SSm14). A mass loss of 3.3% was caused by water at a temperature of 25-120° C. Thermal decomposition of the salt was observed at temperatures above 240° C., and the heat flow signal of TGA showed an endothermic reaction at a temperature of about 160° C., which may be caused by the melting of the anhydride of the salt.

[0041] Fig.17 The DSC curve of Camp1 (Exp. ID SSm14) is shown (heating rate is 10°C / min). The DSC exhibits a broad endothermic reaction at temperatures between 25 and 120°C, which may be associated with water loss. A broad endothermic reaction occurs at a temperature of 164°C, which may be associated with the melting of the latent anhydride salt.

[0042] Fig.18 The liquid chromatography-mass spectrometry analysis of Camp1 (Exp. ID SSm14) is shown. The purity of the active ingredient is 100%.

[0043] Fig.19 Overlay of H-NMR spectra (500 MHz, DMSO-d6) of ABN401 free base (green) and Camp1 (Exp. ID SSm14) (red) is shown. Peaks corresponding to CI at 9.3, 3.0, 2.7, 2.6 and 2.3 ppm and between 2.0 and 0.8 ppm are fluorescently labeled.

[0044] Fig. 20 Shown are high performance X-ray crystallography (HT-XRPD) patterns of Camp2 (Exp. ID SSm60) before (lower) and after (upper) exposure to AAC (40°C / 75%RH) for 2 days.

[0045] FIG21 shows TGA (A) and TGMS (B) analysis of Camp2 (Exp. ID SSm60) (heating rate 10° C. / min). A mass loss of 1.6% was caused by water at a temperature of 25-80° C. Thermal decomposition of the salt was observed at temperatures above 240° C., and the heat flow signal of TGA showed a significant endothermic reaction at a temperature of about 200° C., which may be caused by the melting of the anhydride of the salt.

[0046] Fig. 22 The DSC curve of Camp2 (Exp. ID SSm60) is shown (heating rate is 10°C / min). The DSC exhibits a broad endothermic reaction at a temperature of 25-70°C, which may be related to water loss. A broad endothermic reaction occurs at a temperature of 208.9°C, which may be related to the melting of the latent anhydride salt.

[0047] Figure 23 shows TGA (A) and TGMS (B) analysis of Camp2 (Exp. ID SSm60) after further drying for 1 hour at 80°C under vacuum (heating rate 10°C / min). A mass loss of 1.6% due to water occurred at 25-70°C.

[0048] Fig.24The liquid chromatography mass spectrometry analysis of Camp2 (Exp. ID SSm60) is shown. The purity of the active ingredient is 100%.

[0049] Fig.25 Overlay of H-NMR spectra (500 MHz, DMSO-d6) of ABN401 free base (green) and Camp2 (Exp. ID SSm60) (red) is shown. Peaks corresponding to CI at 9.3, 3.0, 2.7, 2.6 and 2.3 ppm and between 2.0 and 0.8 ppm are fluorescently labeled.

[0050] Fig.26 The high-efficiency X-ray crystallography (HT-XRPD) pattern (upper) and the high-resolution X-ray crystallography (HR-XRPD) pattern (lower) of Mes2 (Exp. ID SSm71) are shown.

[0051] Figure 27 shows TGA (A) and TGMS (B) analysis of Mes2 (Exp. ID SSm71) (heating rate 10°C / min). A mass loss of 3.9% due to water occurred at a temperature of 25-110°C. Thermal decomposition of the salt was observed at a temperature of about 240°C, and the heat flow signal of TGA showed an endothermic reaction at a temperature of 210°C, which may be caused by the melting of the anhydride of the salt.

[0052] Fig.28 The DSC curve of Mes2 (Exp. ID SSm71) is shown (heating rate is 10°C / min). The DSC exhibits a broad endothermic reaction at a temperature of 25-110°C, which may be related to water loss. A double endothermic reaction occurs at a temperature of 205-217°C, which may be related to the melting of the anhydride salt.

[0053] Fig.29 The liquid chromatography mass spectrometry analysis of Mes2 (Exp. ID SSm71) is shown. The purity of the active ingredient is 99.6%.

[0054] Fig.30 Overlay of H-NMR spectra (500 MHz, DMSO-d6) of ABN401 free base (blue), Mes2 (Exp. ID SSm5) (green) and Mes2 (Exp. ID SSm71) (red) is shown. The peak corresponding to CI at 2.3 ppm is fluorescently labeled.

[0055] FIG. 31 shows the change in mass (A) and isothermal change (B) of Mes2 (Exp. ID SSm71) measured by DVS.

[0056] Fig.32The high-efficiency X-ray crystallography (HT-XRPD) pattern (upper) and the high-resolution X-ray crystallography (HR-XRPD) pattern (lower) of Camp2 (Exp. ID SSm73) are shown.

[0057] FIG33 shows TGA (A) and TGMS (B) analysis of Camp2 (Exp. ID SSm73) (heating rate 10° C. / min). A mass loss of 1.6% due to water occurred at a temperature of 25-80° C. Thermal decomposition of the salt was observed at a temperature of about 240° C., and the heat flow signal of TGA showed an endothermic reaction at a temperature of 200° C., which may be caused by the melting of the anhydride of the salt.

[0058] Fig.34 The DSC curve of Camp2 (Exp. ID SSm73) is shown (heating rate is 10°C / min). The DSC exhibits a broad endothermic reaction at 25-80°C, which may be related to water loss. Other endothermic reactions occur at 208.6°C, which may be related to the melting of the anhydride salt.

[0059] Fig.35 The liquid chromatography mass spectrometry analysis of Camp2 (Exp. ID SSm73) is shown. The purity of the active ingredient is 99.7%.

[0060] Fig.36 Overlay of H-NMR spectra (500 MHz, DMSO-d6) of ABN401 free base (blue), Camp2 (Exp. ID SSm60) (green) and Camp2 (Exp. ID SSm73) (red) is shown. Peaks corresponding to CI at 9.3, 3.0, 2.7, 2.6 and 2.3 ppm and between 2.0 and 0.8 ppm are fluorescently labeled.

[0061] FIG. 37 shows the change in mass (A) and isothermal change (B) of Camp2 (Exp. ID SSm73) measured by DVS.

[0062] Fig.38 High-performance X-ray crystallography (HT-XRPD) patterns of camphorsulfonate (Exp. IDSSm73) before (Camp2, bottom) and after (Camp4, top) DVS analysis are shown.

[0063] Figure 39 shows the results of TGMS analysis (heating rate of 10°C / min) of (A) Form A (Exp. ID GEN78) exposed to 25°C / 60% RH for 1 month and (B) Form A (Exp. ID GEN74) exposed to 40°C / 75% RH for 1 month. Before thermal decomposition at a temperature of about 230°C, 3.7% and 4.0% mass loss were observed due to water, respectively.

[0064] Figure 40 shows the results of TGMS analysis (heating rate of 10°C / min) of (A) Form A (Exp. ID GEN79) exposed to 25°C / 60% RH for 3 months and (B) Form A (Exp. ID GEN75) exposed to 40°C / 75% RH for 3 months. Before thermal decomposition, 4.1% and 4.4% mass losses were observed respectively due to water.

[0065] Figure 41 shows the results of TGMS analysis (heating rate of 10°C / min) of (A) Form A (Exp. ID GEN80) exposed to 25°C / 60% RH for 15 months and (B) Form A (Exp. ID GEN77) exposed to 40°C / 75% RH for 15 months. Before thermal decomposition at a temperature of about 230°C, 3.3% and 3.7% mass loss were observed due to water, respectively.

[0066] Figure 42 shows the results of TGMS analysis (heating rate of 10°C / min) of (A) Form A (Exp. ID GEN81) exposed to 25°C / 60% RH for 24 months and (B) Form A (Exp. ID GEN76) exposed to 40°C / 75% RH for 24 months. Before thermal decomposition, 5.3% and 5.2% mass loss were observed respectively due to water.

[0067] Fig.43 Shown is the LC-MS analysis of Form A (Exp. ID GEN81) exposed to 25°C / 60%RH for 24 months. The purity of the active ingredient is 87.2%.

[0068] Fig.44 Shown is the LC-MS analysis of Form A (Exp. ID GEN76) exposed to 40°C / 75%RH for 24 months. The purity of the active ingredient is 90.7%.

[0069] Fig.45Overlapping high-efficiency X-ray crystallography of Mes2 (Exp.ID SSm71) is shown, from bottom to top showing Mes2 (Exp.ID GEN66) exposed to 25°C / 60% RH for 1 month, Mes2 (Exp.ID GEN70) exposed to 40°C / 75% RH for 1 month, Mes2 (Exp.ID GEN67) exposed to 25°C / 60% RH for 3 months, Mes2+peak (Exp.ID GEN71) exposed to 40°C / 75% RH for 3 months, Mes2+peak (Exp.ID GEN68) exposed to 25°C / 60% RH for 15 months, Mes4+peak (Exp.ID GEN73) exposed to 40°C / 75% RH for 15 months, Mes6 (Exp.ID GEN69) exposed to 25°C / 60% RH for 24 months, Mes6 (Exp.ID GEN70) exposed to 40°C / 75% RH for 3 months, GEN72) after exposure to 40°C / 75%RH for 24 months. The orange fluorescent lines in the vertical section indicate additional refractive peaks at 15.1° and 16.5° 2θ that appeared after the sample was exposed to 40°C / 75%RH for 3 months and 15 months.

[0070] Figure 46 shows the results of TGMS analysis (heating rate of 10°C / min) of Mes2 (Exp. ID GEN66) exposed to 25°C / 60%RH for 1 month (A) and Mes2 (Exp. ID GEN70) exposed to 40°C / 75%RH for 1 month (B). Before thermal decomposition at a temperature of about 230°C, 8.0% and 10.8% mass loss were respectively shown due to water. The heat flow signal showed a loss due to water and a broad endothermic reaction corresponding to the melting point around about 215°C.

[0071] Figure 47 shows the results of TGMS analysis (heating rate of 10°C / min) of Mes2 (Exp. ID GEN67) exposed to 25°C / 60%RH for 3 months (A) and Mes2 (Exp. ID GEN71) exposed to 40°C / 75%RH for 3 months (B). Before thermal decomposition at a temperature of 230°C, 7.7% and 11.2% mass losses were respectively shown due to water. The heat flow signal showed a loss due to water and a broad endothermic reaction corresponding to the melting point around 210°C.

[0072] Figure 48 shows the results of TGMS analysis (heating rate of 10°C / min) of Mes2 (Exp. ID GEN68) exposed to 25°C / 60%RH for 15 months (A) and Mes2 (Exp. ID GEN73) exposed to 40°C / 75%RH for 15 months (B). Before thermal decomposition at a temperature of about 230°C, 6.5% and 9.6% mass loss were respectively shown due to water. The heat flow signal showed loss due to water and a broad endothermic reaction corresponding to the melting point around about 210°C.

[0073] Figure 49 shows the results of TGMS analysis (heating rate of 10°C / min) of Mes2 (Exp. ID GEN69) exposed to 25°C / 60% RH for 24 months (A) and Mes2 (Exp. ID GEN73) exposed to 40°C / 75% RH for 72 months (B). The mass losses due to water were 8.6% and 12.0%, respectively. The heat flow signal showed an endothermic reaction during the loss due to water.

[0074] Fig.50 Shown is the LC-MS analysis of Mes2 (Exp. ID GEN66) exposed to 25°C / 60%RH for 1 month. The purity of the active ingredient is 99.7%.

[0075] Fig.51 Shown is the LC-MS analysis of Mes2 (Exp. ID GEN70) exposed to 40°C / 75%RH for 1 month. The purity of the active ingredient is 97.2%.

[0076] Fig.52 Shown is the LC-MS analysis of Mes2 (Exp. ID GEN67) exposed to 25°C / 60%RH for 3 months. The purity of the active ingredient is 99.6%.

[0077] Fig.53 Shown is the LC-MS analysis of Mes2 (Exp. ID GEN71) exposed to 40°C / 75%RH for 3 months. The purity of the active ingredient is 99.5%.

[0078] Fig.54 Shown is the LC-MS analysis of Mes2 (Exp. ID GEN68) exposed to 25°C / 60%RH for 15 months. The purity of the active ingredient is 100%.

[0079] Fig.55 Shown is the LC-MS analysis of Mes2 (Exp. ID GEN73) exposed to 40°C / 75%RH for 15 months. The purity of the active ingredient is 100%.

[0080] Fig.56 Shown is the LC-MS analysis of Mes2 (Exp. ID GEN69) exposed to 25°C / 60%RH for 24 months. The purity of the active ingredient is 99.6%.

[0081] Fig.57 Shown is the LC-MS analysis of Mes2 (Exp. ID GEN72) exposed to 40°C / 75%RH for 24 months. The purity of the active ingredient is 100%.

[0082] Fig.58 Overlapping high-efficiency X-ray crystallography of Camp2 (Exp. ID SSm73) is shown, from bottom to top showing Camp2 (Exp. ID GEN50) exposed to 25°C / 60% RH for 1 month, Camp2 (Exp. ID GEN54) exposed to 40°C / 75% RH for 1 month, Camp2 (Exp. ID GEN51) exposed to 25°C / 60% RH for 3 months, Camp4 (Exp. ID GEN55) exposed to 25°C / 60% RH for 3 months, Camp2 (Exp. ID GEN52) exposed to 25°C / 60% RH for 15 months, Camp4 (Exp. ID GEN56) exposed to 40°C / 75% RH for 15 months, Camp2 (Exp. ID GEN53) exposed to 25°C / 60% RH for 24 months, Camp3+E (Exp. ID GEN57) after exposure to 40°C / 75%RH for 24 months.

[0083] Figure 59 shows the results of TGA analysis (heating rate of 10°C / min) of Camp2 (Exp. ID GEN50) exposed to 25°C / 60%RH for 1 month (A) and Camp2 (Exp. ID GEN54) exposed to 40°C / 75%RH for 1 month (B). Before thermal decomposition at a temperature of about 240°C, 1.6% and 1.8% mass loss were respectively shown due to water.

[0084] FIG60 shows the results of TGA analysis (heating rate of 10°C / min) of Camp2 (Exp. ID GEN51) exposed to 25°C / 60%RH for 3 months (A) and Camp2 (Exp. ID GEN55) exposed to 40°C / 75%RH for 3 months (B). Before thermal decomposition at a temperature of about 240°C, 1.6% and 1.8% mass losses were respectively shown due to water. The heat flow signal showed an endothermic reaction at a temperature of about 200°C in GEN50 and an endothermic reaction at a temperature of about 150°C in GEN55, and a widespread endothermic reaction occurred in the subsequent portion corresponding to the discharge of water.

[0085] FIG61 shows the results of TGA analysis (heating rate of 10°C / min) of Camp2 (Exp. ID GEN52) exposed to 25°C / 60%RH for 15 months (A) and Camp2 (Exp. ID GEN56) exposed to 40°C / 75%RH for 15 months (B). Before thermal decomposition at a temperature of about 240°C, 1.6% and 6.9% mass losses were respectively shown due to water. The heat flow signal showed an endothermic reaction at a temperature of about 200°C in GEN52 and at a temperature of about 150°C in GEN56, and a widespread endothermic reaction occurred in the subsequent portion corresponding to the discharge of water.

[0086] FIG62 shows the results of TGA analysis (heating rate of 10°C / min) of Camp2 (Exp. ID GEN53) exposed to 25°C / 60%RH for 24 months (A) and Camp2 (Exp. ID GEN57) exposed to 40°C / 75%RH for 24 months (B). The mass losses due to water were 1.9% and 6.7%, respectively. The heat flow signal showed an endothermic reaction at a temperature of about 150°C in GEN57, and a broad endothermic reaction occurred in the subsequent portion corresponding to the discharge of water.

[0087] Fig.63 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN50) exposed to 25°C / 60% RH for 1 month. The purity of the active ingredient is 99.8%.

[0088] Fig.64 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN54) exposed to 40°C / 75%RH for 1 month. The purity of the active ingredient is 99.8%.

[0089] Fig.65 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN51) exposed to 25°C / 60%RH for 3 months. The purity of the active ingredient is 99.7%.

[0090] Fig.66 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN55) exposed to 40°C / 75%RH for 3 months. The purity of the active ingredient is 99.3%.

[0091] Fig.67 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN52) exposed to 25°C / 60%RH for 15 months. The purity of the active ingredient is 97.3%.

[0092] Fig.68 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN56) exposed to 40°C / 75%RH for 15 months. The purity of the active ingredient is 93.7%.

[0093] Fig.69 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN53) exposed to 25°C / 60%RH for 15 months. The purity of the active ingredient is 100%.

[0094] Fig.70 Shown is the LC-MS analysis of Camp 2 (Exp. ID GEN57) exposed to 40°C / 75%RH for 15 months. The purity of the active ingredient is 88.6%. DETAILED DESCRIPTION

[0095] The methanesulfonate salt, which is a novel salt of the compound, effectively inhibits the activity of c-Met tyrosine kinase, and can be usefully used as a therapeutic agent for various hyperproliferative diseases associated with excessive cell proliferation and growth due to abnormal kinase activity, such as cancer, psoriasis, rheumatoid arthritis, diabetic retinopathy, etc. Also provided is a pharmaceutical composition for inhibiting c-Met tyrosine kinase activity and a pharmaceutical composition for preventing or treating a hyperproliferative disorder, comprising the novel salt compound as an active ingredient.

[0096] In one aspect, the mesylate is the S-enantiomer of the triazolopyrazine derivative represented by the chemical formula 1. Preferably, the triazolopyrazine derivative represented by the chemical formula 1 is an optically pure substance. In another aspect, the optical purity is at least 95%, at least 97%, at least 99% or substantially 100%.

[0097] In one aspect, the mesylate is formed in one of the forms of Mes1, Mes2 or Mes3. The mesylate is likely to exist in the form of Mes2. In one aspect, the mesylate has a physical stability of at least 2 days at 20-50°C and 35-80% relative humidity. In one aspect, the mesylate has a physical stability of 24 months under ambient conditions. And, the purity of the active ingredient of the mesylate is at least 95%, and the purity is preferably about 100%.

[0098] In one aspect, the high-performance X-ray powder diffraction (HT-XRPD) pattern of the mesylate salt is composed of characteristic peaks at 2θ of 15.5-16.0°, 2θ of 17.5-18.0° and 2θ of 21.5-22.0° (deg). It is inferred that the HT-XRPD of the mesylate salt actually has the following characteristic peaks.

[0099]

[0100]

[0101] or

[0102]

[0103] In one aspect, the present invention provides a method for preparing the mesylate salt. The method comprises: step a), adding the compound of Chemical Formula 1 to a reactor containing a solvent; step b), stirring the solvent and the compound in the reactor; step c), adding methanesulfonic acid to the solution prepared in step b); and step d), cooling the solution prepared in step c) to precipitate the mesylate salt.

[0104] In one aspect, the solvent may be selected from acetonitrile, acetone, 1-2-dimethoxyethane, n-heptane, isopropanol, water or tetrahydrofuran (THF). In one aspect, the methanesulfonic acid added to the solution prepared in step b) is added in an equivalent of 1:1.5 to 1:2.5 relative to the compound of chemical formula 1. Preferably, the equivalent ratio is 1:1.9 to 1:2.3, and the solvent is acetonitrile. In one aspect, the step b) is performed at a temperature of about 45°C to 55°C for at least 1 hour.

[0105] In one aspect, the present invention provides a pharmaceutical composition comprising the mesylate and a pharmaceutical carrier. The pharmaceutically acceptable carrier contained in the pharmaceutical composition is one or more components selected from the group consisting of lactose, glucose, sucrose, sorbitol, mannitol, starch, gum arabic, calcium phosphate, alginate, gelatin, calcium silicate, microcrystalline cellulose, polyvinyl pyrrolidone, cellulose, water, syrup, methylcellulose, methyl hydroxybenzoate, propyl hydroxybenzoate, talc, magnesium stearate and mineral oil. In addition to the above ingredients, the pharmaceutical composition provided by the present invention may also include lubricants, wetting agents, sweeteners, flavoring agents, emulsifiers, suspending agents, preservatives, etc.

[0106] In one aspect, the present invention provides a method for reducing the activity of c-Met kinase by administering a pharmaceutical composition containing an effective amount of the mesylate salt to a patient in need thereof. In one aspect, the patient is a patient suffering from a disease associated with excessive cell proliferation and activation, for example, the disease may be lung cancer, colorectal cancer, pancreatic cancer, rectal cancer, ovarian cancer, kidney cancer, prostate cancer or brain tumor. In one aspect, the method is a method for treating or preventing excessive cell proliferation and activation.

[0107] <General>

[0108] Table 1

[0109]

[0110]

[0111] <Solvent>

[0112] Table 2

[0113] ACN Acetonitrile IPA 2-Propanol MTBE Tert-Butyl methyl ether Tetrahydrofuran (THF) Tetrahydrofuran

[0114] <Counter ions> Table 3

[0115]

[0116]

[0117] The present invention will be described in detail by the following examples, but the technical scope of the present invention is not limited to the examples.

[0118] Example

[0119] The compound of Chemical Formula 1 (ABN-401) was provided by ABION, and the other compounds were provided by Fisher Scientific, Sigma Aldrich or VWR. The compounds used were of researcher grade, and the solvents used for LCMS analysis were of LCMS grade.

[0120] Determine solubility

[0121] Solubility was determined by adding small aliquots of solvent (50 μL up to 1 mL, 100 μL above 1 mL) to the starting material until complete dissolution occurred or a maximum volume of 4 ml was reached.

[0122] Then, the solid obtained after evaporating the solvent was analyzed by HT-XRPD, and the experimental results and details thereof are shown in Table 1.

[0123] (Form 1)

[0124] Table 4

[0125]

[0126]

[0127] Thermal stability

[0128] Thermal stability experiments of ABN-401 were performed to confirm the chemical stability of the dissolved starting material when exposed to elevated temperatures.

[0129] A solution of ABN-401 with a concentration of about 0.3 mg / mL was prepared in a solvent consisting of acetone, 1,2-dimethoxyethane, and acetonitrile. The solution was exposed to room temperature for 1 hour, and then two sample aliquots were sequentially exposed to temperatures of 50°C and 80°C for 1 hour, respectively. The solution was analyzed by LCMS.

[0130] Furthermore, the sample placed at room temperature for 24 hours was measured again to examine the chemical deterioration of the compound over time.

[0131] No serious chemical deterioration of the samples was observed at the temperatures of 50° C. and 80° C. The results are shown in Table 2.

[0132] (Table 2) LCMS analysis results in thermal stability experiment

[0133] Table 5

[0134]

[0135]

[0136] Salt screening experiment

[0137] The ABN-401 solutions in acetone, 1,2-dimethoxyethane and acetonitrile were prepared at concentrations of about 25, 13 and 8 mg / ml, respectively, and the salt screening experiment was initiated.

[0138] Counterions were added to the API solution at a ratio of 1:1.1, 1:2.1, and 1:3.1. The experiment resulted in a temperature profile that included three heating-cooling cycles between 5°C and 50°C, and aging at 25°C for 3 days ( Figure 1 ).

[0139] After the aging time was over, the solid particles were separated from the liquid phase and dried under reduced pressure at 50° C. and then analyzed by HT-XRPD.

[0140] The solution and mother liquor phase were evaporated at room temperature and the remaining solid particles were analyzed by HT-XRPD. All solid particles were then exposed to accelerated aging conditions of 40°C / 75%RH for 48 hours and re-measured by HT-XRPD to test their physical stability.

[0141] Scaling up salt

[0142] The mesylate salt Mes2 was scaled up to 0.5 gram level (Exp. ID SSm71). 500 mg of the free base form was dissolved in 23 ml of acetone at a concentration of 26 mg / ml at room temperature.

[0143] Methanesulfonic acid (1 M in water) was added to give a molar ratio of API:CI of 1:2.1. Precipitation of the salt was observed after addition of the counterion. The suspension was heated to 50°C and stirred at 50°C for 8 hours. The salt suspension was cooled to 25°C. The solid particles were isolated and dried under reduced pressure at 50°C, 10 mbar, and then analyzed by HT- / HR-XRPD, TGA / TGMS, DSC, LCMS, 1H-NMR and DVS.

[0144] Camphorsulfonate salt Camp2 was scaled up to 0.3 gram scale (Exp. ID SSm73). 300 mg of the free base form was dissolved in 15 ml of ACN to a concentration of 20 mg / ml. 136 mg of camphor-10-sulfonic acid was added to give a molar ratio of API:CI of 1:1.1. Stirring was continued at 50°C for 1 hour to dissolve the counterions, the solution was cooled to 25°C and aged for 72 hours. Precipitation of the salt occurred during the cooling curve, the solid precipitate was isolated and then dried under reduced pressure at 50°C, 10 mbar and analyzed by HT- / HR-XRPD, TGA / TGMS, DSC, LCMS, 1H-NMR and DVS.

[0145] Physical and chemical stability

[0146] The methanesulfonate (Mes2), camphorsulfonate (Camp2) and maleate (Mae2) salts were subjected to physical stability tests at specific temperature and relative humidity (25° RH and 40° RH) for 2 years.

[0147] The above stability test was also performed on the free base form of ABN-401 as a reference material.

[0148] The vials containing the particles were subjected to XRPD, TGMS and HPLC tests at 1, 3, 15 and 24 months to confirm whether there were any particular changes in the solid particles and the water and solvent contents, and to confirm whether the storage state of the compound was deteriorated when stored under different conditions.

[0149] Table 3: Conditions used for stability testing of the camphorsulfonate (Camp2), maleate (Mae2), mesylate (Mes2) and free base form (FB) of ABN-401

[0150] Table 6

[0151]

[0152]

[0153] High efficiency X-ray powder diffraction

[0154] HT-XRPD patterns were collected by a Crystal T2 high performance XRPD apparatus.

[0155] The plate was mounted on a Bruker General Area Detector Diffraction System (GADDS) equipped with a VANTEC-500 gas area detector for correction of intensity and shape. The accuracy calibration of the peak positions was performed according to the NIST SRM1976 standard (Corundum).

[0156] Data collection was performed at room temperature using a Cu Ka monochromator with a 2θ range of 1.5° to 41.5°, which is the most unique method for XRPD patterns. The diffraction patterns of each well were collected by exposing each frame for 90 seconds in two 2θ ranges (1.5°≤2θ≤21.5° first frame, 19.5°≤2θ≤41.5° second frame).

[0157] The XRPD pattern is subjected to any operation to remove background or smooth the curve.

[0158] The support material used during HT-XRPD measurements is transparent to X-rays and contributes only very slightly to the background.

[0159] High-resolution X-ray powder diffraction analysis

[0160] Powder data were collected by D8 diffraction analysis, here using Cu with monochromated germanium at room temperature.

[0161]

[0162] The data were collected using a LynxEye detector for solids at 22 sec / step over a 2θ range of 4° to 45° and a 2θ step size of 0.016°. The sample was measured using a glass capillary with an outer diameter of 0.3 mm and a length of 8 mm.

[0163] TGMS analysis

[0164] The mass loss due to the loss of water and solvent in the crystals was determined by TGA. The weight of the sample was monitored and heated with a TGA / DSC3+STARe system to obtain a weight-temperature curve and a heat flow signal as the result. The TGA / DSC3+ results were temperature corrected using indium and aluminum samples. The sample was loaded into a 100 μL aluminum crucible and sealed. A filling hole was formed in the seal, and the crucible was heated from 25°C to 300°C at a heating rate of 10° during the TGA process. Dry nitrogen was used during the purge.

[0165] The gases emitted from the TGA samples were analyzed by an Omnistar GSD 301T2 (Pfeiffer Vacuum GmbH, Germany) mass spectrometer. The analyzer can perform mass analysis at temperatures in the range of 0-200 amu.

[0166] DSC analysis

[0167] DSC thermograms were recorded by a heat flux DSC3+STARe system. The DSC3+ was calibrated for temperature and enthalpy using trace amounts of indium (mp=156.6°; δHf=28.45 J / g) and zinc (mp=419.6°; δHf=107.5 J / g).

[0168] The sample was sealed in a standard 40 μL aluminum pan and filled with a well, and heated during DSC from 25° C. to 300° C. at a heating rate of 10°. Dry nitrogen was used during the purge at a flow rate of 50 mL / min.

[0169] H-NMR analysis

[0170] H-NMR spectra were recorded at room temperature using a 500 MHz Bunker instrument. The samples were dissolved in DMSO and analyzed. The data were processed using the ACD Labs software Spectrus processor.

[0171] LCMA analysis

[0172] Characterization of the starting material and purification of the new crystalline form from the free base form

[0173] Method name: S19061_0.3M

[0174] Sample: 0.3 mg / ml concentration, diluent: acetonitrile

[0175] (Form 4)

[0176] Table 7

[0177]

[0178] Analysis and purification of new crystalline salt

[0179] Method name: S19061_01.M

[0180] Sample: 0.3 mg / ml concentration, diluent: acetonitrile / water (50 / 50)

[0181] (Form 5)

[0182] Table 8

[0183]

[0184] DVS Analysis

[0185] The difference in hygroscopicity of different forms of solid substances is a measure of the relative stability of each substance when the relative humidity increases. The isothermal hygroscopicity of trace samples is obtained by the DVS-1 system. The device is suitable for measuring very trace samples with an accuracy of 0.1 μg. At a constant temperature of 25°C, the relative humidity (40-95-40% RH) is changed in the process of hygroscopicity-dehumidification-hygroscopicity, usually each step (10% relative humidity step) is maintained for 60 minutes. At the end of the DVS experiment, the sample is measured by XRPD.

[0186] Hygroscopicity is classified according to the European Pharmaceutical Hygroscopicity Classification.

[0187] At 25°C / 80%RH (24 hours), the moisture absorption rate was graded as follows.

[0188] Mass change <0.2% - non-hygroscopic

[0189] Mass change > 0.2% and < 2% - slightly hygroscopic

[0190] Mass change >2% and <15% - slightly hygroscopic

[0191] Mass change > 15% - Very hygroscopic

[0192] Methanesulfonate

[0193] Figure 4XRPD patterns of all mesylate salts are shown for the free base form (Form A).

[0194] Mes1 is the mesylate salt obtained by adding methanesulfonic acid to the three crystallization solvents to make the molar ratio of API:CI 1:1.

[0195] Table 6 shows the experimental conditions used to obtain Mes1. The solid selected for subsequent characterization was the crystalline salt formed when methanesulfonic acid was added in acetone at 1 molar equivalent (Exp. ID SSm4). Mes1 showed physical stability after exposure to AAC (40° RH) for 2 days.

[0196] (Table 6): Experimental conditions used to obtain Mes1. * indicates the solid formed after evaporation of the solvent.

[0197] Table 9

[0198]

[0199] TGA / TGMS analysis of Mes 1 showed a mass loss of 4.3% due to acetone and water at a temperature of 140° C., according to the MS signal. Thermal decomposition was observed at temperatures above 230° C.

[0200] The heat flow signal of TGA shows a broad endothermic reaction due to mass loss around 160°C, which is related to the melting of the anhydrous form. The thermal analysis results indicate that Mes1 is a complex of hydrated / dissolved crystalline salt.

[0201] Mes2 is a mesylate obtained in an experiment in which methanesulfonic acid was added to three crystallization solvents to give a molar ratio of API:CI of 1:2 and added to ACN to give a ratio of 1:3. Table 7 shows the experimental conditions for obtaining Mes12. The solid selected for subsequent characterization is the crystalline salt (Exp. ID SSm5) formed when methanesulfonic acid was added in acetone at 2 molar equivalents. Mes2 exhibited physical stability after 2 days of exposure to AAC (40°RH).

[0202] (Table 7): Experimental conditions used to obtain Mes2

[0203] Table 10

[0204]

[0205] TGA / TGMS analysis of Mes2 showed a potential mass loss of 4.6% (4.6% is equivalent to 2.0 water molecules per salt molecule) between 25 and 150°C based on the MS signal. Thermal decomposition was observed at temperatures above 220°C.

[0206] The heat flow signal of the TGA shows a broad endothermic reaction due to water loss, and an endothermic reaction is shown around 210°C, which is related to the melting of the anhydride. The thermal analysis results indicate that Mes2 is a dihydrate of dimethanesulfonate.

[0207] The DSC analysis results of Mes2 showed a broad endothermic reaction from 25°C to 120°C, which may be related to the loss of water. A double absorption reaction occurred around 218.2°C, which may be caused by the melting of the potential anhydrous salt, followed by an exothermic reaction at 223°C, which may be caused by thermal decomposition.

[0208] The chemical purity of the Mes2 determined by LCMS was 100%, which confirmed the presence of the API in the solid phase of Mes2.

[0209] The results of 1H-NMR analysis of Mes2 are shown in Fig.11 The shift of API resonances seen in the spectrum of Mes2 indicated a proton transfer from the acidic counterion to the free base. The API:CI ratio was shown to be 1:2, with residual acetone observed at 2.2 ppm.

[0210] Mes3 is a mesylate obtained by adding methanesulfonic acid in acetone and 1,2-dimethoxyethane solvents to give an API:CI molar ratio of 1:3. The solid selected for the subsequent characterization process is the crystalline salt formed when methanesulfonic acid is added in acetone at 3 molar equivalents (Exp.ID SSm6). Table 8 shows the experimental conditions used to obtain Mes3. Although the crystalline form is maintained, Mes3 exhibits solubility when exposed to AAC (40°RH) for 2 days.

[0211] (Table 8): Experimental conditions used to obtain Mes3

[0212] Table 11

[0213]

[0214] TGA / TGMS analysis of Mes3 showed a mass loss of 5.6% due to water between 25 and 140°C based on the MS signal (5.6% corresponds to 2.8 water molecules per salt molecule). Thermal decomposition was observed at temperatures above 220°C.

[0215] The heat flow signal of the TGA shows a broad endothermic reaction due to water loss at about 200°C, followed by thermal decomposition. The thermal analysis results indicate that Mes3 is a hydrated crystalline salt.

[0216] Camphorsulfonate

[0217] Fig.14 HT-XRPD patterns of the camphorsulfonate salt and the starting material (Form A) are compared.

[0218] Camp1 is the salt form obtained by adding camphor-10-sulfonic acid in acetone and 1,2-dimethoxyethane solvents so that the molar ratio of API:CI is 1:1 and the experiment is carried out. Table 9 shows the experimental conditions used to obtain Camp1. The solid selected for the subsequent characterization process is the crystalline salt formed when camphor-10-sulfonic acid is added in acetone at 1 molar equivalent (Exp.ID SSm14). Camp1 is physically stable when exposed to AAC (40°RH) for 2 days.

[0219] (Table 9): Experimental conditions used to obtain Camp1

[0220] Table 12

[0221]

[0222] TGA / TGMS analysis of Camp 1 showed a mass loss of 3.3% due to water between 25 and 150°C based on the MS signal (3.3% corresponds to 1.5 water molecules per salt molecule). Thermal decomposition was observed at temperatures above 240°C.

[0223] In the heat flow signal, an obvious endothermic reaction is shown around 160°C, which may be related to the melting of the acid anhydride of the salt.

[0224] The DSC analysis results of Camp 1 showed a broad endothermic reaction from 25°C to 120°C, which may be related to the loss of water. An endothermic reaction occurred around 164.0°C, which may be caused by the melting of the underlying anhydrous salt.

[0225] The chemical purity of Camp1 determined by LCMS was 100%, which confirmed the presence of API in the solid phase of Camp1.

[0226] The 1H-NMR analysis results of Camp1 are shown in Fig.19 The shift of API resonances seen in the spectrum of Camp 1 indicated a proton transfer from the acidic counterion to the free base. The API:CI ratio was shown to be 1:1, with residual acetone observed at 2.1 ppm.

[0227] Camp2 is a salt form obtained by adding camphor-10-sulfonic acid to ACN solvent to make the molar ratio of API:CI 1:1 and conducting an experiment (Exp. ID SSm60). Table 10 shows the experimental conditions used to obtain Camp2. Camp2 is physically stable when exposed to AAC (40° RH) for 2 days.

[0228] (Table 10): Experimental conditions used to obtain Camp2

[0229] Table 13

[0230]

[0231] TGA / TGMS analysis of Camp 2 showed a mass loss of 1.6% due to water between 25 and 100°C based on the MS signal (1.6% corresponds to 0.7 water molecules per salt molecule). Thermal decomposition was observed at temperatures above 240°C.

[0232] In the heat flow signal, an endothermic reaction is shown around 200°C, which may be related to the melting of the anhydride of the salt, followed by decomposition.

[0233] The DSC analysis results of Camp 2 showed a broad endothermic reaction from 25°C to 70°C, which may be related to the loss of water. An endothermic reaction was shown around 208.9°C, which may be related to the melting of the anhydrous salt.

[0234] The sample of Camp2 (Exp. ID SSm60) was dried under reduced pressure at 80°C to prevent the melting of the potential anhydride at 208.9°C shown in the DSC results. The solid particles were then analyzed by HT-XRPD and TGMS. Camp2 remained in the solid particles and contained 1.9% water.

[0235] The chemical purity of Camp2 determined by LCMS was 100%, which confirmed the presence of API in the solid phase of Camp2.

[0236] The 1H-NMR analysis results of Camp2 are shown in Fig.25 The shift of API resonances that appears in the spectrum of Camp2 indicates a proton transfer from the acidic counterion to the free base, indicating that the API:CI ratio is 1:1.

[0237] Characterization and analysis results of Mes2

[0238] HT-XRPD analysis results confirmed the crystallization of Mes2 (Exp. ID SSm71) in the scale-up experiment. The high-resolution XRPD (HR-XRPD) pattern of Mes2 was not indexed.

[0239] TGA / TGMS analysis of dried Mes2 showed a gradual mass loss of 4.0% between 25 and 110°C, which was presumed to be due to water loss based on the MS signal (4.0% is equivalent to 1.8 water molecules per salt molecule). Thermal decomposition of Mes2 was observed at temperatures above 240°C.

[0240] The DSC analysis results of Mes2 showed that there was a broad endothermic reaction associated with water loss between 25 and 110°C. The double endothermic reaction observed between 205 and 217°C was probably related to the melting of the salt. The chemical purity of Mes2 determined by LCMS was 99.6%, which confirmed the presence of API in the solid phase of Mes2.

[0241] The results of H-NMR analysis of Mes2 are shown in Fig.30 The shift in the API resonance observed in the Mes2 spectrum indicates a proton transfer from the acidic counterion to the free base. The API:CI ratio is 1:2.

[0242] FIG31 shows the results of the DVS measurement of Mes2. The first moisture absorption of the half cycle shows that the water absorption reaches 29.6% at a relative humidity of 95% (a mass change of 24.8% occurs when the relative humidity changes from 40 to 95%). In the dehumidification cycle from 95 to 0% relative humidity, water is discharged. In each stage change of relative humidity, the absorption of water is not balanced (each stage is balanced for 1 hour), which is the reason for the hysteresis that occurs at relative humidities between 95 and 70% in the absorption-dehumidification cycle. The absorption of water is reversible.

[0243] The mass loss at 80% relative humidity was about 12.2%. As a result, the mesylate Mes2 is considered slightly hygroscopic in the European Classification of Hygroscopicity of Pharmaceuticals. The solid morphology did not change after the DVS analysis.

[0244] Characterization and analysis results of Camp2

[0245] HT-XRPD analysis results confirmed the crystallization of Camp2 (Exp. ID SSm73) in the scale-up experiment. The high-resolution XRPD (HR-XRPD) pattern of Camp2 was not indexed.

[0246] TGA / TGMS analysis of dried Camp2 showed a mass loss of 1.6% between 25 and 80°C, which was speculated to be due to water loss based on the MS signal (1.6% is equivalent to 0.7 water molecules per salt molecule). Thermal decomposition of Camp2 was observed at temperatures above 240°C.

[0247] The DSC analysis results of Camp2 showed that there was a broad endothermic reaction associated with water loss between 25 and 80 °C. A second obvious endothermic reaction was observed at a temperature of 208.6 °C, which may be related to the melting process of the anhydrous salt. The chemical purity of Camp2 determined by LCMS was 99.7%, which confirmed the presence of API in the solid phase of Camp2.

[0248] The H-NMR analysis results of Camp2 are shown in Fig.36 The shift in the API resonance observed in the Camp2 spectrum indicates a proton transfer from the acidic counterion to the free base. The API:CI ratio is 1:1.

[0249] Figure 37 shows the results of the DVS measurement of Camp2. The first moisture absorption of the half cycle showed that the water absorption rate reached 15.6% at a relative humidity of 95% (a mass change of 14.1% occurred when the relative humidity changed from 40 to 95%). The curve representing the mass change shows that the absorption of water did not reach equilibrium at a relative humidity of 90-95%. In the dehumidification cycle from 95 to 0% relative humidity, water was discharged. The mass change in the second half of the absorption cycle (from 0 to 40% relative humidity) was 6.6%. The absorption of water is irreversible, which indicates a change in form. The new form of Camp ( Fig.38 ).

[0250] The DVS analysis results showed that the mass change at 80% relative humidity was about 1.4%, which indicates that the substance is slightly hygroscopic according to the European Classification of Hygroscopicity of Pharmaceuticals.

[0251] Stability of the free base form

[0252] Form A was exposed to 25°C / 60% RH and 40°C / 75% RH for 3 months for TGA analysis, and the results are shown in Fig.40a , Fig.40b The samples exposed to 25°C / 60%RH and 40°C / 75%RH for 3 months showed a mass loss of 4.1% and 4.4%, respectively. The heat flow analysis results showed that an extensive endothermic reaction due to water loss occurred at a temperature of 140°C corresponding to the melting of Form A. Thermal decomposition of both samples was observed at a temperature of 230°C.

[0253] Form A was exposed to 25°C / 60% RH and 40°C / 75% RH for 15 months and TGA analysis was performed and the results are shown in Fig.41a , Fig.41b The samples exposed to 25°C / 60%RH and 40°C / 75%RH for 15 months showed a mass loss of 3.3% and 3.7%, respectively. The heat flow analysis results showed that an extensive endothermic reaction due to water loss occurred at a temperature of 140°C corresponding to the melting of Form A. Thermal decomposition of both samples was observed at a temperature of 230°C.

[0254] Form A was exposed to 25°C / 60% RH and 40°C / 75% RH for 24 months and TGA analysis was performed and the results are shown in Fig.42a , Figure 42b The samples exposed to 25°C / 60%RH and 40°C / 75%RH for 24 months showed a mass loss of 5.3% and 5.2%, respectively. The heat flow analysis results showed that an extensive endothermic reaction due to water loss occurred at a temperature of 140°C corresponding to the melting of Form A. No thermal decomposition occurred at temperatures below 200°C.

[0255] The Form A was exposed to 25°C / 60%RH (Exp. ID GEN81) and 40°C / 75%RH (Exp. ID GEN76) for 24 months, and the chemical purity determined by LCMS was 87.2% and 90.7%, respectively ( Fig.43 , 44). This confirms that the compound changes under both conditions.

[0256] Stability of the mesylate salt

[0257] HT-XRPD analysis results confirm that solid form transformation occurs after exposure of Mes2 to 25°C / 60%RH and 40°C / 75%RH. The change occurs faster at 40°C / 75%RH than at 25°C / 60%RH. After 3 months of exposure of Mes2 samples to 25°C / 60%RH, there is no significant difference in the powder pattern, but after 15 months, additional diffraction peaks at 2θ of 15.1° and 16.5° were detected. It is possible that the diffraction peaks are caused by changes in other crystalline forms, but the nature of their shape is unclear.

[0258] The sample exposed to 40°C / 75%RH showed additional peaks after 3 months. After 15 months, all XRPD peaks shifted and were designated Mes4, with the additional peaks at 15.1° and 16.5° still present in 2θ. After 24 months, the solid exposed to both conditions transformed into a new form, which was designated Mes6. Fig.45Shown is the scale-up of Mes2 and the overlay of the powder patterns after exposure to 25°C / 60%RH and 40°C / 75%RH for 1, 3, 15, and 24 months.

[0259] Figures 46A and 46B show the results of TGA analysis of Mes2 samples after exposure to 25°C / 60%RH and 40°C / 75%RH for 1 month. 8.0% water loss occurred in the sample exposed to 25°C / 60%RH for 1 month, and 10.8% water loss occurred in the sample exposed to 40°C / 75%RH for 1 month. Both samples thermally decomposed at a temperature of 230°C. Compared with the initially determined moisture content of Mes2, both samples showed significant water absorption (3.9%).

[0260] The water absorption still occurred after 3 months. Figures 47A and 47B show that the water loss after 3 months of exposure to 25°C / 60%RH and 40°C / 75%RH was 7.7% and 11.2%, respectively.

[0261] The thermal changes of the samples after exposure to storage conditions for 15 months showed almost the same results as the above samples, although the mass loss was very small. Figures 48A and 48B show that the water loss after exposure to 25°C / 60%RH and 40°C / 75%RH for 15 months was 6.5% and 9.6%, respectively.

[0262] After 24 months, Mes2 showed a mass loss of about 8.6% and 12.0% after incubation at 25°C / 60%RH and 40°C / 75%RH, respectively. Similar thermal changes were recorded in the heat flow signal. An endothermic reaction started at a temperature of 200°C, which was considered to be caused by the thermal decomposition of the mesylate.

[0263] After the Mes2 was exposed to 25°C / 60%RH (Exp. ID GEN66) and 40°C / 75%RH (Exp. ID GEN70) for 1 month, the chemical purity determined by LCMS was 100% and 99.7%, respectively. Fig.50 , Fig.51 ). This confirmed the presence of API in the solid phase of Mes2 in a purity almost similar to that of the original Mes2 salt.

[0264] The chemical purity of Mes2 measured after exposure to 25°C / 60%RH and 40°C / 75%RH for 3 months was 99.6% and 99.5%, respectively ( Fig.52 , Fig.53 ).

[0265] The chemical purity of the samples after exposure to 25℃ / 60%RH and 40℃ / 75%RH for 15 months was 100% ( Fig.54 , Fig.55The chemical purity of the samples after exposure to 25℃ / 60%RH and 40℃ / 75%RH for 24 months was 99.6% and 100% respectively ( Fig.56 , Fig.57 ).

[0266] Stability of Camphorsulfonate

[0267] HT-XRPD analysis results confirmed that no conversion of Camp2 to a solid form occurred after exposure to 25°C / 60% RH for 24 months.

[0268] However, at 40°C / 75%RH, a transformation of the solid phase was observed after 3 months. The new powder pattern was named Camp4 powder pattern. More transformation occurred after 24 months, indicating that the camphorsulfonate and free base forms of Form E may be mixed. Fig.58 Shown is the scale-up of Camp 2 and the overlay of the powder patterns after exposure to 25°C / 60%RH and 40°C / 75%RH for 1, 3, 15, and 24 months.

[0269] After exposing the Mes2 sample to 25°C / 60%RH for 3 months, there was no particular difference in the powder pattern, but after 15 months, additional diffraction peaks were detected at 2θ of 15.1° and 16.5°. It is possible that the diffraction peaks are caused by changes in other crystalline forms, but the nature of their shapes is unclear.

[0270] The sample exposed to 40°C / 75%RH showed additional peaks after 3 months. After 15 months, all XRPD peaks shifted and were designated Mes4, with the additional peaks at 15.1° and 16.5° still present in 2θ. After 24 months, the solid exposed to both conditions transformed into a new form, which was designated Mes6. Fig.45 Shown is the scale-up of Mes2 and the overlay of the powder patterns after exposure to 25°C / 60%RH and 40°C / 75%RH for 1, 3, 15, and 24 months.

[0271] Figures 59A and 59B show the TGA analysis results after Camp2 was exposed to 25°C / 60%RH and 40°C / 75%RH for 1 month. The sample exposed to 25°C / 60%RH for 1 month showed a mass loss of 1.6%, and the sample exposed to 40°C / 75%RH for 1 month showed a mass loss of 1.8%.

[0272] Both samples thermally decomposed at temperatures above 240 °C.

[0273] The Camp2 sample incubated for 3 months at 25°C / 60%RH showed a water content similar to that recorded after 1 month, indicating no significant water absorption under said conditions. However, at 40°C / 75%RH, a transformation from Camp2 to Camp4 solid form was observed. As a result, the TGA analysis results showed a water content of 7.1% (3.3 water molecules per camsylate molecule). The thermal changes recorded in the heat flow signal showed a broad endothermic reaction due to water dissolution, followed by an endothermic reaction due to the melting of the anhydride at a temperature of 150°C (200°C for Camp2).

[0274] The Camp2 sample cultured at 25°C / 60%RH for 24 months showed a mass loss of 1.9%, which is similar to the mass loss determined in the above formula (Figure 62A). This result indicates that no significant water absorption occurs under the conditions described. The TGA analysis results after exposure to 40°C / 75%RH for 24 months showed a water content of 6.7% (3.2 water molecules per camsylate molecule). The thermal changes recorded in the heat flow signal showed a broad endothermic reaction due to water dissolution, followed by an endothermic reaction due to the melting of the anhydride at a temperature of 150°C (200°C for Camp2).

[0275] The chemical purity of the two samples of Camp2 determined by LCMS after exposure to 25°C / 60%RH (Exp. ID GEN50) and 40°C / 75%RH (Exp. ID GEN54) for 1 month was 99.8% ( Fig.63 , Fig.64 ). This indicates that the API is present in the solid phase of Camp2. The chemical purity after 3 months is compared with that of the 1 month sample ( Fig.65 , Fig.66 )

[0276] The chemical purity of Camp2 after exposure to 25°C / 60%RH for 15 months was 99.5% ( Fig.67 ), indicating that Camp2 is stable for at least 15 months under the conditions described. The chemical purity of the Camp4 sample after exposure to 40°C / 75%RH for 15 months was 93.7% ( Fig.68 ). This indicates that Camp 2 is converted to Camp 4 at 40°C / 75%RH.

[0277] The chemical purity of Camp2 after exposure to 25°C / 60%RH for 24 months was 100% ( Fig.69), which confirms that Camp2 is stable under the conditions for at least 24 months. The chemical purity of the camphorsulfonate salt after exposure to 40°C / 75%RH for 24 months was 88.6%, indicating that chemical deterioration occurs at 40°C / 75%RH when Camp2 is converted to other forms.

[0278] The present invention is described with reference to the specific embodiments, but it is obvious that various modifications can be made without departing from the technical concept of the present invention. Therefore, it is known that the present invention is not limited to the above embodiments, but also includes the following claims and equivalents.

[0279] Industrial Applicability

[0280] The present invention has industrial applicability.

Claims

1. A mesylate, characterized in that It is composed of methanesulfonic acid and a triazolopyrazine derivative represented by the following chemical formula 1: Chemical formula 1:

2. The mesylate according to claim 1, characterized in that The mesylate salt is the S-enantiomer of the triazolopyrazine derivative of Chemical Formula 1.

3. The mesylate according to claim 2, characterized in that The mesylate salt is an optically pure triazolopyrazine derivative of Chemical Formula 1.

4. The mesylate according to any one of claims 1 to 3, characterized in that The mesylate salt is any one of Mes1, Mes2 and Mes3.

5. The mesylate according to claim 4, characterized in that The mesylate salt is Mes2.

6. The mesylate according to claim 1, characterized in that The mesylate salt has a physical stability of at least 2 days at a temperature of 20°C to 50°C and a relative humidity of 35% to 80%.

7. The mesylate according to claim 6, characterized in that The API purity of the mesylate salt is at least 95%.

8. The mesylate according to claim 7, characterized in that The API purity of the mesylate salt was 100%.

9. The mesylate according to claim 1, characterized in that The high-efficiency XRPD spectrum of the mesylate salt exhibits characteristic peaks at 2θ of 15.5° to 16.0°, 2θ of 17.5° to 18.0°, and 2θ of 21.5° to 22.0°.

10. The mesylate according to claim 1, characterized in that The high-efficiency XRPD pattern of the mesylate salt actually has the following characteristic peaks: or 11. A method for preparing the mesylate according to claim 1, characterized in that: The preparation method comprises: Step a), adding a compound of the following chemical formula 1 into a reactor containing a solvent; Chemical formula 1: Step b), stirring the compound and the solvent in a reactor; Step c), adding methanesulfonic acid to the solution in step b); and Step d), cooling the solution of step c) to obtain a precipitate of mesylate.

12. The method for preparing the mesylate according to claim 11, characterized in that: The solvent includes any one selected from acetonitrile, acetone, 1,2-dimethoxyethane, n-heptane, isopropanol, water or tetrahydrofuran.

13. The method for preparing the mesylate according to claim 12, characterized in that: Relative to the compound of Chemical Formula 1, the methanesulfonic acid added in step b) is added in an equivalent of 1:1.5 to 1:2.

5.

14. The method for preparing the mesylate according to claim 13, characterized in that: The equivalent is 1:1.9 to 1:2.3, and the solvent is acetonitrile.

15. The method for preparing the mesylate according to any one of claims 11 to 14, characterized in that: The step b) is performed at a temperature of 45°C to 55°C for at least 1 hour.

16. A pharmaceutical composition, characterized in that The method comprises the mesylate according to claim 1 and a pharmaceutically acceptable carrier.

17. The pharmaceutical composition according to claim 16, characterized in that The pharmaceutically acceptable carrier is selected from one or more of the group consisting of lactose, glucose, sucrose, sorbitol, mannitol, starch, gum arabic, calcium phosphate, alginate, gelatin, calcium silicate, microcrystalline cellulose, polyvinyl pyrrolidone, cellulose, water, syrup, methylcellulose, methyl hydroxybenzoate, propyl hydroxybenzoate, talc, magnesium stearate and mineral oil.

18. The pharmaceutical composition according to claim 17, characterized in that The pharmaceutical composition further comprises at least one selected from the group consisting of a lubricant, a wetting agent, a sweetener, a flavoring agent, an emulsifier, a suspending agent and a preservative.

19. A method for inhibiting the activity of c-Met kinase, characterized in that: The method comprises injecting an effective amount of the mesylate salt of claim 1 into a subject.

20. The method for inhibiting the activity of c-Met kinase according to claim 19, characterized in that: The subject exhibits a dysproliferative disorder.

21. The method for inhibiting the activity of c-Met kinase according to claim 20, characterized in that: The abnormal proliferative disease is any one selected from lung cancer, colorectal cancer, pancreatic cancer, rectal cancer, ovarian cancer, kidney cancer, prostate cancer and brain tumor.